The Influence of the Problem Based Learning Model Assisted by Video Based Laboratory on Students Ability to Solve Problem on Elasticity and Hooke’s Law - Yunus, Ingkawati; Odja, Abdul Haris; Buhungo, Trisnawaty Junus (Kasuari: Physics Education Journal (KPEJ), 2024)
This study aims to determine the significant effect of the problem based learning model assisted by video based laboratory on students' problem solving abilities in improving problem solving abilities on the material of elasticity and Hooke's law. The type of research is an experiment with a one group pretest posttest research design. The population in the study were students of SMAN 1 Bonepantai consisting of two classes, namely class XI 1 as the experimental class and class XI 2 as the replication class. The instrument used was a descriptive test consisting of 6 questions that had been validated. Data were analyzed using the one sample t test. Based on the results of the study, the average posttest value of the experimental class was 84.5 and the replication class was 82.8. The results of data analysis using the t test showed that the application of the problem based learning model in the form of a video based laboratory had a significant effect on students' problem solving abilities on the material of elasticity and Hooke's law.